Neuroticism Drives Associations Between Repetitive Behaviors and Depression in Autistic Adults - Schwartzman, Jessica M.; Williams, Zachary J.; Richards, Jared K.; Mattheiss, Samantha R.; Gotham, Katherine O. (Frontiers in Psychiatry, 2022)
Depression is more prevalent among autistic adults than neurotypical adults (Hollocks et al., 2019), yet risk factors are incompletely understood in this population. Some research groups have focused on relationships between negative repetitive thinking and depression in the autistic population, which may explain elevated prevalence rates in line with general population findings on rumination and internalizing disorders (Nolen-Hoeksema, 2000). Little is known about associations between depression and more prototypical repetitive cognitions and/or behaviors characteristic of autism (i.e., insistence on sameness [IS] and repetitive sensorimotor [RSM] behaviors). Therefore, the present study aimed to examine associations between IS, RSM behaviors, and depressive symptoms in 762 autistic adults, and whether observed effects are confounded by additional factors (e.g., demographic factors, trait neuroticism). To test if greater IS scores were associated with greater depressive symptoms on the BDI-II, a Bayesian linear regression was conducted with BDI-II scores (dependent variable) regressed on age, gender, educational level, RSM scores, and IS scores (independent variables). To test the effects of neuroticism on observed relationships, a second regression was conducted that included all predictors from the baseline model and neuroticism. Standardized regression coefficients were tested against an interval null hypothesis of [-0.1, 0.1] to assess for practical significance. Results indicated that IS exhibited a moderate positive relationship with depressive symptoms, while RSM behaviors provided only a slight increase in predictive ability. However in the second model, neuroticism exhibited a strong positive relationship with depressive symptoms, completely attenuating the effect of IS. Associations between RSM behaviors and depressive symptoms did not meet our criteria for practical significance, particularly when neuroticism was added to the model. Neither RSM nor IS moderated the effect of neuroticism on depression. The findings from this study add to the literature on risk factors in the pathway to depression in autism, and suggest opportunities for clinical translation to screening and intervention efforts. Screening for IS in autistic individuals is a common diagnostic practice in clinical and research settings that may be leveraged to also identify those at higher risk for depression, and increasing flexibility in daily life may promote emotional regulation and distress tolerance.